Evaluation the New Hydro-Pneumatic Damper for Passenger Car using LQR, PID and H-infinity Control Strategies - Abd - Elwahab, M. Rabie; Moaaz, Ahmad O.; Faris, Waleed Fekry; Ghazaly, Nouby M.; Makrahy, Mostafa M. (Automotive Experiences, 2024)
In this study, a mathematical model of a new hydro-pneumatic damper consists of a double-acting cylinder, two oil chambers, a damping valve, and an accumulator is developed to assess its response to vertical vibrations in a passenger car. The main idea of the new damper aim to make that the damping coefficient in compression differ than that in rebound which achieve more stability specially during cornering. The damping coefficient difference in compression and rebound can be achieved due to the presence of accumulator. Both passive and active hydro-pneumatic suspension systems with the new damper employing different control strategies such as LQR, PID, and H-infinity control, are employed to assess the effectiveness of the suspension system. The investigation focuses on vertical acceleration, pitch acceleration, suspension deflection, and dynamic tire load. The half-car model is simulated using MATLAB/Simulink, and the results for both active and passive hydro-pneumatic suspensions are analyzed in terms of frequency, time, and power spectral density responses. The findings reveal that the active suspension system with H-infinity control demonstrates an 81% improvement in body acceleration and a 92% improvement in pitch acceleration (angular acceleration) compared to the passive hydro-pneumatic suspension which improve the stability of the vehicle during cornering. Similarly, the implementation of LQR-controlled suspension enhances body acceleration and step acceleration by approximately 40% and 57%, respectively, compared to the passive hydro-pneumatic suspension. Moreover, when compared to the passive hydro-pneumatic suspension, the PID-controlled active hydro-pneumatic suspension exhibits a 64% improvement in step acceleration and a 44% improvement in body acceleration.